ENVIRONTMENTAL MANAGEMENT ACCOUNTING, COMPETITIVE ADVANTAGE, FIRM PERFOMANCE: INDONESIA’S MANUFACTURING SECTOR. - thomas wijanarko; Peggy Delita Merida (Jurnal Riset Akuntansi, 2021)
Abstrack This study aims to examine the indirect relationship between Environmental Management Accounting (EMA) and Firm Performance through Competitive Advantage. The contribution of this paper is that there is a Competitive Advantage mediating the relationship of EMA and improving firm performance. The study was conducted on 444 manufacturing companies in Indonesia from 2013-2017. The novelty in this study is a research model that makes Competitive Advantage a mediation for EMA and Firm performance variables, and Competitive Advantage variables using market share proxy. The results of this study are EMA has a positive effect on Firm Performance, EMA has a positive effect on Competitive Advantage, Competitive Advantage has a positive effect on Firm Performance, and Competitive Advantage as Quasi Mediating from the influence of EMA on Firm Performance. Abstrak Penelitian ini bertujuan untuk menguji hubungan tidak langsung antara environmental management accounting (EMA) dan kinerja perusahaan (firm performance) terhadap keunggulan kompetitif (competitive advantage). Kontribusi penelitian ini ialah menunjukan keunggulan kompetitif memediasi antara EMA dan meningkatkan kinerja perusahaan. Penelitian ini dilakukan pada 444 perusahaan manufaktur di Indonesia selama 2013-2017. Kebaruan dari penelitian ini penggunaan keunggulan kompetitif sebagai variabel mediasi untuk EMA dan kinerja perusahaan, serta penggunaan pangsa pasar sebagai proksi variabel keunggulan kompetitif. Hasil penelitian ini ialah EMA memiliki pengaruh positif terhadap kinerja perusahaan, keunggulan kompetitif memiliki pengaruh positif terhadap kinerja perusahaan, dan keunggulan kompetitif, keunggulan kompetitif sebagai mediasi semu dari pengaruh EMA terhadap kinerja perusahaan.